Medicaid Access During Economic Distress: Lessons Learned From the Great Recession. (October 2021) - Benitez, Joseph; Perez, Victoria; Seiber, Eric
Medicaid enrollment increases during economic downturns which imply households using the public health insurance program during coverage gaps due to job loss. However, we provide new evidence demonstrating that the Medicaid program's countercyclical protections against economic downturns are largely concentrated in states with more generous Medicaid eligibility criteria for adults. We exploit the timing of the 2007-2009 Great Recession to compare trends in recession-linked Medicaid enrollment between states with more generous Medicaid eligibility guidelines and states with more restrictive guidelines. For similar effects of the recession, Medicaid enrollment grew larger states in with more generous Medicaid programs. Our work suggests for every 100 people becoming unemployed in states with a restrictive Medicaid program, about 96 would be uninsured, and about 11 would enroll in Medicaid. Conversely, about 49 would be uninsured in a state with more generous Medicaid guidelines and 57 would enroll in Medicaid.